Castleman's disease requiring repeat surgical excision - Andrew B. Nordin; Aleksander D. Nordin; Mark A. Ranalli; Brian D. Kenney (Elsevier, 2018)
Castleman's disease is an uncommon lymphoproliferative disorder that can be found in both unicentric and multicentric forms. Although the multicentric form is typically seen in immunocompromised patients, the unicentric variety often presents as an asymptomatic mass in otherwise healthy patients. While these lesions are rare in the pediatric population, recognizing the potential diagnosis may help dictate pre- and intraoperative imaging and operative technique and approach.